Risk Factors for Sexual Violence Among College Students in Dating Relationships: An Ecological Approach. Issue 15 (August 2021) - Bhochhibhoya, Shristi; Maness, Sarah B.; Cheney, Marshall; Larson, Daniel
College students in dating relationships are vulnerable to sexual violence given that nine out of 10 acts of sexual violence are perpetrated by acquaintances, friends, or dating partners. Although past research has explored the risk factors for sexual violence, few studies have considered multileveled factors associated with sexual violence. This study uses the ecological model to investigate the risk factors for sexual violence among college students in dating relationships. Domains of individual, interpersonal, community, and societal levels were examined for their associations with sexual victimization. A prevalidated survey was conducted among 361 undergraduates in dating relationships from a public university in the south central United States. Chi-square tests and negative binomial regression analysis were conducted. Approximately 35% of the college students reported experiencing some form of sexual violence perpetrated by their dating partner including attempted and completed rapes. College women reported having experienced significantly higher rates of sexual violence in comparison with college men. On the contrary, this study documents the significant higher prevalence of sexual violence among heterosexual students than among lesbian, gay, bisexual, transgender, queer college students for experiencing at least one type of sexual violence or unwanted sexual contacts in a dating relationship. Sexual victimization is associated with gender, sexual assertiveness, the frequency of hookups, peer deviance, parental involvement, and perceived discrimination. Participants' gender, frequent hookups, and lower sexual assertiveness are positively associated with risk of sexual victimization across all types of sexual violence. Multilevel prevention programs and strategies are needed on campuses to reduce sexual victimization among college students in dating relationships.